Challenges Of Sharia Accounting In The Millenial Generation And The Digital Era 4.0 - Charly Marlinda; Melisa Melisa; Dea Natassa; Dhea Amanda Aulia Putri; Nanda Kristia Santoso; Azra Ayue Binti Abdul Rahman (International Journal of Management Research and Economics, 2024)
This research aims to determine the challenges of sharia accounting in the millennial generation and the digital era 4.0. The method used in this research is a qualitative method with a systematic review approach. The results of this research conclusion are the main challenges faced in implementing sharia accounting in the millennial generation and the digital era 4.0 including technology adaptation, data security, education and awareness, product innovation, and compliance with sharia principles in financial transactions. The millennial generation, which is increasingly dominant in the market, plays a role in changing consumer patterns, while digital technology 4.0 influences the way business and financial transactions are carried out.